Xeno-Free Integrated Platform for Robust Production of Cardiomyocyte Sheets from hiPSCs. (23rd November 2022) - Dias, Tiago P.; Baltazar, Tânia; Pinto, Sandra N.; Fernandes, Tiago G.; Fernandes, Fábio; Diogo, Maria Margarida; Prieto, Manuel; Cabral, Joaquim M. S.
Abstract : Human induced pluripotent stem cells (hiPSCs) can be efficiently differentiated into cardiomyocytes (CMs), which can be used for cardiac disease modeling, for drug screening, and to regenerate damaged myocardium. Implementation of xeno-free culture systems is essential to fully explore the potential of these cells. However, differentiation using xeno-free adhesion matrices often results in low CM yields and lack of functional CM sheets, capable of enduring additional maturation stages. Here, we established a xeno-free CM differentiation platform using TeSR/Synthemax, including a replating step and integrated with two versatile purification/enrichment metabolic approaches. Results showed that the replating step was essential to reestablish a fully integrated, closely-knit CM sheet. In addition, replating contributed to increase the cTnT expression from 65% to 75% and the output from 2.2 to 3.1 CM per hiPSC, comparable with the efficiency observed when using TeSR/Matrigel. In addition, supplementation with PluriSin1 and Glu - Lac + medium allowed increasing the CM content over 80% without compromising CM sheet integrity or functionality. Thus, this xeno-free differentiation platform is a reliable and robust method to produce hiPSC-derived CMs, increasing the possibility of using these cells safely for a wide range of applications.